Fieldwork in the human services : theory and practice for field educators, practice teachers and supervisors - Cooper, Lesley; Briggs, Lynne (Allen and Unwin, 2000)
Teaching, learning and assessment in the field. The responsibilities of fieldwork management. Practical suggestions.